The violence of the Mexico´s global south as performance - et. al., Vite Pérez, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective of the article is to interpret violence as a symbolic social action (performance). Method. Analysis through the binary narrative established by its protagonists, which has a meaning organized by an imaginary structure shared collectively, which turns out to be alien to social reality, but constructed through the discourse of Mexican public insecurity. At the same time, information from the written press was used not as a resource for power; rather, as a binary narrative that expresses motives, relationships, and institutions. Theory. It is used in the so-called civil sphere, visualized as a set of values ​​and beliefs, synthesized as ideals, linked to citizen rights in a democratic society. Findings / Conclusions.